The effectiveness of using scramble games in improving speaking skills in Arabic language learning in Madrasah Tsanawiyah Banyuwangi - Faslah, Redho; Abidin, Munirul; Yuris, Penny Respati (Abjadia : International Journal of Education, 2025)
Educational games such as Scramble can enhance student learning, particularly in Arabic language education. Improving learning outcomes has become one of the main focuses in the field of education. This study aims to analyze the effectiveness of using Scramble games in improving students' speaking skills and learning interest in Arabic language learning.This research employs a quantitative method with a quasi-experimental design. The research sample consists of eighth-grade students from Madrasah Tsanawiyah Mukhtar Syafaat Blokagung Banyuwangi, divided into two groups: experimental and control. Data was collected through tests and questionnaires. The results of this study indicate that the comparison between pre-test and post-test shows an average N-gain of 76.9. The hypothesis test results show a significant value of 0.00, which is smaller than 0.05, leading to the rejection of Ho and acceptance of Ha. Based on these findings, the use of Scramble games significantly improves students' speaking skills in learning Arabic.